Study on the behavior of high-strength friction-grip bolts under combined shear and tensile forces. (November 2022) - Zhang, Yujie; Zhang, Junping; Liu, Airong; Chen, Bingcong; Safaei, Babak; Yang, Zhicheng
Abstract: In order to investigate the shear behaviors of high-strength friction-grip bolts (HSFGBs) under combined shear and tensile forces in steel-SFRC composite beams, eight pull-out specimens with HSFGBs were fabricated and tested. Initial slip force, initial shear stiffness, post slipping stiffness, ultimate shear strength and ultimate slipping of HSFGBs were reasonably defined to quantitatively evaluate the shear behaviors of HSFGBs. Then, finite element models were carefully established and calibrated against test data using ABAQUS software. The influence of tensile force on the shear performance of HSFGBs was also discussed. Load transfer and failure mechanisms of HSFGBs and their influences on the shear behavior of HSFGBs under different tensile forces were analyzed. An improved interaction equation was derived for the calculation of HSFGB ultimate strength under combined shear and tensile forces. The obtained results indicated that both shear deformation and necking phenomenon of HSFGBs occurred under combined shear and tensile forces. Initial slip force, initial shear stiffness, post slipping stiffness and ultimate shear strength of HSFGBs were found to decrease with the increase of tensile force. HSFGB axial stress was first increased and then decreased with the increase of tensile force. In addition, HSFGB shear stress was only slightly changed under different tensile forces. Furthermore, improved interaction expression accurately predicted shear strength of HSFGBs under combined shear and tensile forces.